A Case-Control Study for the Effectiveness of Oral Zinc in the Prevention and Mitigation of COVID-19 - Gordon, Antonio M.; Hardigan, Patrick C. (Frontiers in Medicine, 2021)
Background: The ongoing coronavirus disease-19 (COVID-19) pandemic (caused by an infection with severe acute respiratory syndrome (SARS)-coronavirus (CoV-2) has put a burden on the medi-cal community and society at large. Efforts to reduce the disease burden and mortality over the course of the pandemic have focused on research to rapidly determine age-stratified seroepidemio-logic surveys, a centralized research program to fast-track the most promising rapid diagnostics and serologic assays, and the testing of potential anti-viral agents, immunologic therapies, and vaccine candidates. Despite the lack of official recognition for the role of nutrition in the fight against COVID-19 infection, multiple groups proposed zinc supplementation as an adjuvant for the man-agement of participants. Method: In an ambulatory, interventional, prospective, single-blind study, we evaluated the effec-tiveness of zinc supplementation in the prevention and mitigation of COVID-19 in two similar par-ticipant groups. In Clinic A (n =104) participants were randomized to receive 10 mg, 25 mg, or 50 mg zinc picolinate daily, and Clinic B control participants paired according to their demographics and clinical parameters (n=96). All participants were compared based on demographics, clinical comorbidities, blood counts, renal functions, vitamin D levels, and their development of sympto-matic COVID-19 infection. Results: Symptomatic COVID-19 infection was significantly higher among the control group partici-pants (N=9, 10.4%) than the treatment participants (N=2, 1.9%), p = 0.015. The unadjusted odds ratio indicates that symptomatic COVID-19 infection was 5.93 [95% CI: 1.51, 39.26] higher in the control group, p < 0.01. Controlling for co-morbidities, individuals in the control group were 7.38 (95% CI: 1.80,50.28) times more likely to develop symptomatic COVID-19 infection as compared with individuals in the treatment group (p < 0.01). Discussion: The findings from our study suggest that zinc supplementation in all three doses (10, 25, and 50 mg) may be an effective prophylaxis of symptomatic COVID-19 and may mitigate the severity of COVID-19 infection. Conclusion: Zinc is a relatively inexpensive mineral nutrient that may be an effective prophylactic agent to prevent and mitigate the potentially deadly symptomatic SARS-CoV-2 infection.